Upgrading bio-oil from waste cooking oil by esterification using SO42−/ZrO2 as catalyst. (15th September 2020) - Yu, Shitao; Wu, Shasha; Li, Lu; Ge, Xiaoping
Abstract: High-acid value of bio-oil from biomass is the important reason to restrict its application. Here acid value of bio-oil from waste cooking oils (WCO) was decreased by methyl esterification with the FFAs (Free Fatty Acids) in the bio-oil using SO4 2- /ZrO2 as a solid acid catalyst. The acid value of the esterification product decreased to 3 mg KOH g −1, and both the kinematic viscosity and the density reached the 0 # diesel standard. Other properties were superior to traditional biodiesel, and the obtained product could be used as a diesel with good performance. The activity and reusability of the SO4 2− /ZrO2 have been studied and the results suggested that the rate of esterification was 96.15% and more than 90% in the fifth esterification. Then kinetics of the reaction has been studied; revealing it to be a zero-order reaction when the methanol is excessive.